Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Kuliah Di Perguruan Tinggi Swasta - ir, masduki; Prihartini, Endah; Abdullah, Dudung (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The community's decision in choosing a university is an activity that requires a lot of consideration. Basically, the decision to choose a university is always related to the marketing process by the party offering the service. This is in line with the opinion of Mulyawan and Sidharta (2013) in Shaleh et al., (2018) which states that service marketing plays an important role in meeting consumer needs, including the need for input in choosing universities. The purpose of the study was to determine the contribution of motivation, attitudes, personality (internal factors), reference groups, family, college image, and promotion via social media (external factors) to the decision to study in private universities. The data analysis technique used Structural Equation Modeling (SEM) with the help of AMOS 21 software. The population in this study was Majalengka University students with a sample of 198 people, and the sampling technique used was proportionate random sampling. The results of the research show that partially motivation, personality, family support, college image, and promotion via social media have a significant contribution to the decision to study in private universities. Meanwhile attitudes and reference groups did not significantly contribute to the decision to study in private universities. The two most dominant factors in contributing to college decisions are family support and college image.